ASSESSMENT OF SEED QUALITY OF DIFFERENT CABBAGE LOTS DURING AGING - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2022)
The aim of the research was to evaluate the influence of the year and the seed lots on the most important indicators of cabbage seed quality. Quality testing of nine different seed lots of Potomac F1 cabbage was performed during three years (2019, 2020 and 2021). Analyses of variance showed a significant effect (p<0.01) of the year (Y), while seed lot (L) and their interaction (Y × L) showed a significant effect (p<0.05) on all observed parameters quality (germination energy, total germination, abnormal seedlings and dead seeds). The strongest correlation between the examined parameters was in the first year and weakened in the second and third years. In the first year as expected, significant positive correlation between germination energy and total germination was found (r = 0.84779, p<0.01). The highly and negative interdependence was achieved between total germination and dead seeds (r = -0.94363, p<0.001) and abnormal seedlings (r = -0.78019, p<0.05). Also negative interdependence was found between germination energy and dead seeds (r = -0.80000, p<0.01) and abnormal seedlings (r = -0.66144, p<0.05). The germination energy and the total germination of the cabbage seeds considered were found to decrease with the increasing seed age, in contrast to the numbers of their abnormal seedlings and dead seeds which continued to increase with seed aging. The obtained results indicate that the germination of highly hybrid conventional cabbage seeds decreases significantly during aging, as a direct consequence of a very significant increase in the number of abnormal seedlings.